(untitled) (CIPEEX, 2025)
Diabetes mellitus is a chronic endocrine-metabolic disease that is treated with medications that improve insulin production or action, or with exogenous insulin administration. Insulin must be stored and handled correctly in order to minimize application errors and ensure successful treatment and glycemic control. Taking this into consideration, the overall objective of this project is to assess the knowledge of physicians working at the Central University Outpatient Clinic (AUC) on the handling and administration of insulin. The assessment was carried out using a questionnaire, which aimed to evaluate errors and correct answers during patient guidance on the handling and administration of insulin. The results showed that the highest error rates were identified in sub-items related to the application technique, insulin homogenization, and possible application sites. On the other hand, the items with the highest accuracy were about contraindications for application in injured areas and the time insulin should be removed from the refrigerator before application and the needle should remain in the tissue. The study revealed gaps in the knowledge of insulin therapy among physicians at the Central University Outpatient Clinic (AUC), highlighting the need for educational interventions aimed at these professionals, in addition to promoting new studies to foster safety and efficacy in the treatment of diabetes mellitus.